and $\alpha - \sqrt{\beta}$.These two are conjugate roots. Here $\alpha$ is a rational number where as $\sqrt{\beta}$ is an irrational number.

As $\alpha + \sqrt{\beta}$ is a root of the quadratic equation, $ax^{2}$ + bx + c = 0 so it satisfies the equation.

So put x = $\alpha + \sqrt{\beta}$ in $ax^{2}$ + bx + c = 0

$a(\alpha + \sqrt{\beta})^{2} + b(\alpha + \sqrt{\beta}$) + c = 0

$a (\alpha^{2} + \beta + 2.\alpha.\sqrt{\beta}) + b.\alpha + b.\sqrt{\beta}$ + c = 0

$a.\alpha^{2} + a.\beta + 2.a.\alpha.\sqrt{\beta} + b.\alpha + b.\sqrt{\beta}$ + c = 0

$a.\alpha^{2} + a.\beta + b.\alpha + c + 2.a.\alpha.\sqrt{\beta} + b.\sqrt{\beta}$ = 0

$a.\alpha^{2} + a.\beta + b.\alpha + c + (2.a.\alpha + b)\sqrt{\beta}$ = 0

$a.\alpha^{2} + a.\beta + b.\alpha + c + (2.a.\alpha + b)\sqrt{\beta} = 0 + 0.\sqrt{\beta}$

∴ $a.\alpha^{2} + a.\beta + b.\alpha$ + c = 0 and 2.a.$\alpha$ + b = 0

Now put x = $\alpha - \sqrt{\beta}$ in the equation $ax^{2}$ + bx + c = 0, we get

$a(\alpha - \sqrt{\beta})^{2} + b(\alpha - \sqrt{\beta}$) + c = 0

$a (\alpha^{2} + \beta - 2.\alpha.\sqrt{\beta}) + b.\alpha - b.\sqrt{\beta}$ + c = 0

$a.\alpha^{2} + a.\beta - 2.a.\alpha.\sqrt{\beta} + b.\alpha - b.\sqrt{\beta}$ + c = 0

$a.\alpha^{2} + a.\beta + b.\alpha + c - 2.a.\alpha.\sqrt{\beta}- b.\sqrt{\beta}$ = 0

$a.\alpha^{2} + a.\beta + b.\alpha + c - (2.a.\alpha + b)\sqrt{\beta}$ = 0

$a.\alpha^{2} + a.\beta + b.\alpha + c - (2.a.\alpha + b)\sqrt{\beta} = 0 - 0.\sqrt{\beta}$

From the above we can see that the equation $ax^{2}$ + bx + c = 0 is satisfied by $\alpha - \sqrt{\beta}$ when $\alpha + \sqrt{\beta}$ is a surd of the equation. Now its clear that if one root of the equation $ax^{2}$ + bx + c = 0 is $\alpha + \sqrt{\beta}$ then the other irrational root is $\alpha - \sqrt{\beta}$. Thus, ($\alpha +\sqrt{\beta}$) and ($\alpha - \sqrt{\beta}$) are conjugates roots. So quadratic equation irrational roots are occur in pairs.

$\alpha = 1 + \sqrt{3}$ and $\beta = 1 - \sqrt{3}$

∴ sum of roots = $\alpha + \beta = 1 + \sqrt{3} + 1 - \sqrt{3}$ = 2

Product of roots = $\alpha . \beta = (1 + \sqrt{3}) (1 - \sqrt{3})$ = 1- 3 = -2

The quadratic equation,

$x^{2}$ + (sum of roots).x + Product of roots = 0

$x^{2} - (\alpha + \beta).x + \alpha . \beta$ = 0

$x^{2}$ - 2x - 2 = 0

∴ Required quadratic equation is $x^{2}$ - 2x - 2 = 0

2) Find the quadratic equation with rational coefficients which has

5 - 2$\sqrt{5}$ as a root.

5 + 2$\sqrt{5}$.

$\alpha = 5 - 2\sqrt{5}$ and $\beta = 5 + 2\sqrt{5}$

∴ sum of roots = $\alpha + \beta = 5 - 2\sqrt{5} + 5 + 2 \sqrt{5}$ = 10

Product of roots = $\alpha . \beta = (5 - 2\sqrt{5}) (5 + 2\sqrt{5})$ = 25 -20 = 5

The quadratic equation,

$x^{2}$ + (sum of roots).x + Product of roots = 0

$x^{2} - (\alpha + \beta).x + \alpha . \beta$ = 0

$x^{2}$ - 10x + 5 = 0

∴ Required quadratic equation is $x^{2}$ - 10x + 5 = 0

From Irrational roots of quadratic equation to Home

GMAT

GRE

1st Grade

2nd Grade

3rd Grade

4th Grade

5th Grade

6th Grade

7th grade math

8th grade math

9th grade math

10th grade math

11th grade math

12th grade math

Precalculus

Worksheets

Chapter wise Test

MCQ's

Math Dictionary

Graph Dictionary

Multiplicative tables

Math Teasers

NTSE

Chinese Numbers

CBSE Sample Papers